2011
DOI: 10.15835/nbha3926382
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Diversity in Watermelon Cultivars and Related Species Based on AFLPs and EST-SSRs

Abstract: The genetic relationships among 27 watermelon cultigens (Citrullus lanatus var. lanatus) from different countries of origin and with different horticultural characteristics and 5 related wild-type species and subspecies (Citrullus colocynthis, Citrullus lanatus var. citroides, and Citrullus rehmii) were assessed using amplified fragment length polymorphism (AFLP) and expressed sequence tag-simple sequence repeat (EST-SSR) markers. AFLPs were evaluated using 16 EcoRI-MseI primer combinations, and 862 alleles (a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 18 publications
(15 reference statements)
2
10
0
1
Order By: Relevance
“…A similar distinct clustering pattern of wild and cultivated watermelon genotypes has also been reported by Hwang et al (2011), who clustered 32 watermelon genotypes into two major clusters based on AFLP and EST-SSR markers. In the present study, the genetic relationship based on three different approaches (NJ dendrogram, PCoA and population structure analysis) gave similar results.…”
Section: Genetic Diversity Of Wild and Cultivated Germplasmsupporting
confidence: 80%
“…A similar distinct clustering pattern of wild and cultivated watermelon genotypes has also been reported by Hwang et al (2011), who clustered 32 watermelon genotypes into two major clusters based on AFLP and EST-SSR markers. In the present study, the genetic relationship based on three different approaches (NJ dendrogram, PCoA and population structure analysis) gave similar results.…”
Section: Genetic Diversity Of Wild and Cultivated Germplasmsupporting
confidence: 80%
“…According to high genetic similarity values and low private band among studied different watermelon ecotypes from different region this hypothesis was confirmed that watermelon ecotypes may have been originated from the common ancestry. High genetic similarity among watermelon ecotypes can be due to artificial selection by humans over a long duration breeding programs, improved by sequential selection of the best traits (Kwon et al 2010) and due to the asexual propagation of the species (Hwang et al 2011). Thus, the present results indicated the robustness of the ISSR technique in providing a higher degree of resolution for discriminating closely related genotypes within the species of watermelon.…”
Section: Cluster Analysismentioning
confidence: 54%
“…lanatus ) and the wild C. colocynthis was very high (Hwang et al. ). The wild‐type accessions had round and white fruits in common and diverse rind colors, seed sizes, and seed colors.…”
Section: Discussionmentioning
confidence: 99%
“…Hwang et al. () used EST–SSR markers to differentiate six watermelon cultigens, Citrullus lanatus var. citroides and C. colocynthis based on fruit characteristics.…”
Section: Introductionmentioning
confidence: 99%